2005
DOI: 10.1111/j.1365-3156.2005.01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine coverage with hepatitis B and other vaccines in the Colombian Amazon: do health worker knowledge and perception influence coverage?

Abstract: The HB control program in Colombia has achieved good coverage in one of the most endemic areas of the country. However, barriers to vaccination arise from inequities in the distribution of health insurance and inadequate HW knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…However, despite the existence of the vaccine, without proper knowledge among health workers, individuals in the population are less likely to receive the full course of the vaccine because they are not properly informed of the importance of receiving all three doses (Hoz et al 2005). For HCV, there is neither a vaccine nor an approved post exposure prophylaxis regimen (Centers for Disease Control and Prevention 2007); as a result, hepatitis C prevention programs must focus on behavioral interventions (Soto-Salgado et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the existence of the vaccine, without proper knowledge among health workers, individuals in the population are less likely to receive the full course of the vaccine because they are not properly informed of the importance of receiving all three doses (Hoz et al 2005). For HCV, there is neither a vaccine nor an approved post exposure prophylaxis regimen (Centers for Disease Control and Prevention 2007); as a result, hepatitis C prevention programs must focus on behavioral interventions (Soto-Salgado et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the Ministry of Health of Burkina Faso has adopted strategies aimed at reducing the transmission of HBV and HCV, such as the strengthening of infection control in health facilities by vaccinating health care workers against hepatitis B and blood safety measures. However, the anti-HBV vaccination is unfortunately not used in a systematic manner for the protection of health personnel in primary prevention or post-exposure prophylaxis [11]. In our study we found that vaccinations were not always made in the best conditions; there was either a lack of prior testing of vaccinated health workers or incompleteness of the doses received by the latter.…”
Section: Discussionmentioning
confidence: 44%
“…Health workers' knowledge of HBV has been repeatedly described as disappointing by various studies evaluating the knowledge, attitudes and professional risk of contracting hepatitis [7]- [11]. This study allowed us to note that overall the level of knowledge among health workers is good on targeted knowledge.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations